At the root: defining and halting progression of early chronic obstructive pulmonary disease - Martinez,F; Han,M; Allinson,J; Barr,G; Boucher,R; Calverley,PMA; Celli,BR; Christenson,SA; Crystal,RG; Fageras,M; Freeman,CM; Groenke,L; et al. (American Journal of Respiratory and Critical Care Medicine, 2018)
Chronic obstructive pulmonary disease (COPD) is a prevalent, heterogeneous disorder with varying presentation and progression but with a limited number of disease-modifying therapies (1). This marked heterogeneity impedes identification of subpopulations at risk for accelerated progression, thwarting therapeutic advances. Most COPD studies have included populations with mean ages older than 60 years (2). However, it is increasingly evident that lung function trajectories in COPD differ significantly and that differences are detectable in young adulthood (3–5). In this Perspective, we highlight the need to distinguish “early disease” from late “mild disease,” propose an operational definition of early COPD for use in research studies, and attempt to unify current views on potential disease mechanisms. We focus on smoking, the chief etiologic factor for COPD in the industrialized world. Whether pathogenic mechanisms and effective treatments are shared with the sizable fraction of COPD in never-smokers or resulting from biomass fuel, electronic nicotine delivery systems, and other exposures, are separate, significant questions. We argue that refocusing investigation on early COPD could revolutionize understanding and therapies of this leading cause of worldwide death.